A Monte Carlo-based approach to determine effective atomic numbers of low-Z explosives in landmines - Ozsahin, M. T.; Yavas, K.; Toker, O.; Icelli, O. (TAYLOR & FRANCIS LTD, 2025)
Landmines pose significant humanitarian and strategic challenges, threatening both civilian populations and military operations worldwide. This study presents a practical simulation method based on Rayleigh and Compton scattering ratios to determine the effective atomic number of low atomic number (low-Z) explosives used in landmines. Utilizing the Monte Carlo N-Particle (MCNP) simulation program, Rayleigh/Compton scattering ratios were obtained using a Ge(Li) detector at a scattering angle of 115 degrees within a simulated geometry. The simulation results were found to be in good agreement with experimental data, confirming the reliability of the method. Pure elements with atomic numbers ranging from 3 to 20 and various explosives were irradiated with photons of 59.54 keV energy to obtain scattering spectra. The effective atomic numbers calculated using Rayleigh/Compton scattering ratios were compared with five different theoretical methods, yielding consistent results. These findings demonstrate that the proposed method can reliably determine the effective atomic number of low-Z elements and explosives containing these elements. Additionally, the study confirms that MCNP simulations can be effectively utilized in various fields such as defense industry, radiation safety, medical applications, and radiation dosimetry.HIGHLIGHTS The effective atomic numbers of explosives in nine different landmines were determined using the MCNP simulation and compared with conventional methods.The MCNP simulation method offers a more practical and reliable approach for determining the effective atomic numbers of explosives.The Rayleigh-to-Compton scattering ratio was shown to accurately determine the effective atomic numbers of low atomic number materials.This method has significant potential for application in the detection of landmine explosives, providing a more effective alternative to conventional approaches.
Keywords: Land-Mine; MCNP 6.2; Rayleigh/Compton scattering ratio; effective atomic number; COMPTON-SCATTERING; INELASTIC-SCATTERING; RAYLEIGH; RADIATION; ABSORPTION; RATIO; LESS; Nuclear Science & Technology; Physics